Sex reassignment in Islamic Law: the dilemma of transsexuals - Haneef, Sayed Sikandar Shah (Centre for Promoting Ideas, 2011)
Classical Islamic law in terms of assigning legal rules, inter alia, explicitly recognizes four genders among human beings, namely male, female, hermaphrodite, and effeminate male. In this context, the body of rules that regulate male and female behaviors is regarded as normative. Hermaphrodite upon birth are left in limbo until they can be absorbed into any one of the binary gender system upon puberty or else would be regarded as problematic. Effeminate male/transsexuals on the other hand, are expected to contain their psycho-pseudo female tendencies by not becoming erotic. With the advances in the field of medicine, psychology and sociology, the classical fiqhi postulates on transsexuals have been challenged on several grounds including the legitimacy of attempts by transsexuals for sex reassignment. Vast majority of the contemporary Sunni jurists refute it as it is tantamount to a flagrant violation of God`s created human nature while some Sunnis and Shi`ah Imamiyyah validated it. Accordingly, Muslim transsexual, among others, face the acute dilemma of juristic conflicting views on sex-reassignment particularly when emotion runs high on account of sectarianism between its Shi`ah advocates and predominantly Sunni antagonists. This study, therefore, proposes to explores the juridical possibility of such an option in a Sunni context such as Malaysia.